Ilmu Balaghah Melayu: Isu, Prospek dan Cabaran - Abu Hassan Abdul (Universiti Sains Islam Malaysia, 2024)
In contemporary education, the study of Malay Balaghah exists within the fringes of Malay Studies. The understanding, scope and definition of terms in this area rest within the existing old framework, since a real effort to rejuvenate the discipline is yet to be seen. The main problem relates to its high dependency upon western concepts, theories and rhetorical dichotomy; aside from limited research in the area of Malay rhetoric. The Malay Language needs a comprehensive body of knowledge about Balaghah which may permit a more systematic learning to take place. The foundation in generating this body of knowledge requires an analysis of the concepts of the language, literature and the Malay multiethnic culture in the region. In addition, the Islamic values embedded within the Malay classical texts should be employed as the pillars to this body of knowledge. The generating of a Malay Balaghah body of knowledge should be able to address the various issues relating to linguistic studies and modern Malay literature; which have been heavily influenced by secular values and has lost its sense of direction from the original purpose and philosophy of learning the Malay Language and the knowledge relating to it.